The Frequency and Diagnostic Value of Deeper Sections in Histopathology of Non-Cutaneous Small Biopsy Specimens Obtained from a Tertiary Care Hospital - Mohibullah Khan, Fatima Daud, Najma Attaullah, Shaila Mehwish, Nabiha Naeem, Inam-U-Llah, Tanveer Tara, Sudhair Abbas Bangash, Irfan Ullah (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this research is to ascertain the frequency of deeper sections and the diagnostic utility of these sections in non-cutaneous tiny biopsies obtained from a hospital setting. Study Design: Cross-sectional study Place and Duration: This study was carried out at Shaukat Khanum Memorial Hospital Peshawar, Jan 2022 to April 2022 Methods: In this study, there were a total of 100 patients, ranging in age from 16 to 50 years old. Patients who were hospitalized to the oral and maxillofacial department and who had deeper section procedures were considered for inclusion. Following the acquisition of informed and written consent, complete demographic information was obtained. The locations of organs and the levels at which leaks were found were documented for each and every instance. The mean, standard deviation, frequency, and percentages were the metrics that were used to evaluate the categorical variables. All of the data was analysed with SPSS version 22.0. Results: Among the deeper sections, we discovered that cervix cases accounted for 50%, stomach cases accounted for 25%, endometrial cases accounted for 15%, and colorectal cases accounted for 10%. Twenty-six instances 26%, had a deeper section done, with level 4 being the most prevalent. Although in most cases a diagnosis could be determined from the initial slide, in 55 of these cases (55%), further slides were reviewed to look for additional histological features. The goal was to either confirm the diagnosis obtained from the initial slide or raise confidence in that diagnosis. In 55 cases, 39 (70.9%) showed new pathological abnormalities in deeper sections, whereas 16 (29.1%) showed no change in histological features. Conclusion: A more in-depth examination is typically required in order to arrive at a certain diagnosis. Because of this, it is recommended that, regardless of the extent of the lesion, deeper sections be conducted on samples that cannot be consistently detected on ordinary levels, and this approach need to be standardized everywhere in the globe. Keywords: Histopathology, Deeper Sections, Non-cutaneous, Biopsy